Towards a new world: some inconvenient truths for Anglosphere public administration: The IIAS Braibant Lecture 2014. (March 2015) - Pollitt, Christopher
On the global stage, public management has grown up over the past 30 years as a topic dominated by the 'Anglosphere'. Now there are reasons to believe that this era is ending. There are three main reasons for this. First, the dominance of Anglosphere ideas and practices was never as complete as it may sometimes have appeared. Second, the effectiveness of typical Anglosphere reforms has been problematic. Recent scholarship indicates that only a modest proportion of such reforms can show evidence of substantial success. Third, other regions of the world are becoming economically and politically more influential and self-confident, and, in some cases, they also have long administrative traditions of their own. Far from being a reason for dismay, this opening-up offers an opportunity for difficult, but potentially very rewarding debates that will need to run across different cultures and administrative traditions.